The gold standard and the logic of naturalism : American literature at the turn of the century - Michaels, Walter Benn (University of California Press, 1987)
The Gold Standard and the Logic of Naturalism discusses ways of creating value in turn-of-the-century American capitalism. Focusing on such topics as the alienation of property, the invention of masochism, and the battle over free silver, it examines the participation of cultural forms in these phenomena. It imagines a literary history that must at the same time be social, economic, and legal; and it imagines a literature that, to be understood at all, must be understood both as a producer and a product of market capitalism.
Keywords: American fiction -- 20th century -- History and criticism.; Naturalism in literature.; Production (Economic theory) in literature.; Consumption (Economics) in literature.; Capitalism and literature.; Economics in literature.; Historicism.; Naturalisme dans la littérature.; Économie politique dans la littérature.; Capitalisme et littérature.; Roman américain -- 20e siècle -- Histoire et critique.; Consommation (Économie politique) dans la littérature.; Production dans la littérature.; Historicisme.; historicism (theory); LITERARY CRITICISM -- American -- General.; American fiction; Capitalism and literature; Consumption (Economics) in literature; Economics in literature; Historicism; Naturalism in literature; Production (Economic theory) in literature; Littérature américaine -- Thèmes, motifs.; Naturalisme (mouvement littéraire); 1900-1999; Criticism, interpretation, etc.